What Is Inside Viral Beauty Video and How People React to It - Habibah Ramdhani, Fairuz (KnE Social Sciences, 2020)
This paper focuses on explaining and describing the element of beauty viral video created by social media influencers in Youtube along with behavioral decision taken by the audiences after watching it. Behavioral decisions assessed in this study are in form of viewing, liking, and sharing suggested viral videos. Two types of sample videos were used: top three most viewed Youtube videos of three Indonesian mega-beauty influencers and top three most viewed Youtube videos of three Indonesian middle-user influencers. Research applied in this study was based on virality element framework coined by Tyler West. A video-watching experiment was executed. The result shows that despite having myriad number of viewers, viral beauty videos do not contain the same elements as other viral videos. Other than that, the elements do not have relation with behavioral decision taken. However, there is a relation between viral elements and level of influencer. Keywords: beauty video; behavioral decision; social media influencer; viral video; Youtube video